Western European Populations of the Ichneumonid Wasp Hyposoter didymator Belong to a Single Taxon - Frayssinet, Marie; Audiot, Philippe; Cusumano, Antonino; Pichon, Apolline; Malm, Lisa E.; Jouan, Véronique; Vabre, Marin; Malavieille, Serge; Delalande, Magalie; Vargas-Osuna, Enrique; Bourguet, Denis; Volkoff, Anne-Nathalie (Frontiers in Ecology and Evolution, 2019)
Hyposoter didymator (Hymenoptera, Ichneumonidae) is a generalist solitary endoparasitoid of noctuid larvae. In the present work, we tested whether populations of H. didymator were divided in several genetically distinct taxa as described for many other generalist parasitoid species, and whether differences in H. didymator parasitism rates were explained by the insect host species and/or by the plant on which these hosts were feeding on. The genetic analysis of natural populations collected in different regions in France and Spain on 7 insect hosts and 7 host plants (775 individuals) showed that H. didymator populations belong to a unique single taxon. However, H. didymator seems to be somewhat specialized. Indeed, in the fields it more often parasitized Helicoverpa armigera compared to the other host species collected in the present work. Also, H. didymator parasitism rates in field conditions and semi-field experimental studies were dependent on the host plants on which H. armigera larvae are feeding. Still, H. didymator can occur occasionally on non-preferred noctuid species. One hypothesis explaining the ability of H. didymator to switch hosts in natura could be related to fluctuating densities of the preferred host over the year; this strategy would allow the parasitoid to avoid seasonal population collapses.